2014
DOI: 10.1139/cjpp-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

Preventive roles of swimming exercise and pioglitazone treatment on hepatic dysfunction in a rat model of metabolic syndrome

Abstract: Pioglitazone (Pio) and swimming exercise (SE) are insulin sensitisers. This investigation was suggested because of the significant side effects associated with Pio treatment in metabolic syndrome (MetS). This study was, therefore, designed to investigate the preventive role of Pio treatment and SE in terms of efficiency and pathological changes in MetS in a rat model. Sixty male Sprague-Dawley rats were distributed equally among 6 groups: (i) control group (C), (ii) exercised control group (C+E), (iii) Pio-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This contrasts with the effect of exercise in previous studies in other animal models. For example, Sakr et al reported a beneficial effect of swimming exercise on hepatic histological architecture in 16-week old male Sprague-Dawley rats, a rat model of MS (38). In addition, Kapravelou et al showed that an aerobic exercise protocol enhanced the degree of steatosis in Zucker rats.…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with the effect of exercise in previous studies in other animal models. For example, Sakr et al reported a beneficial effect of swimming exercise on hepatic histological architecture in 16-week old male Sprague-Dawley rats, a rat model of MS (38). In addition, Kapravelou et al showed that an aerobic exercise protocol enhanced the degree of steatosis in Zucker rats.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, patients with obesity showed a rapid increase in serum phospho-fetuin-A (Ser312) after a session of exercise, which returned to baseline levels within 24 h. Within 24 h of exercise, the glucose and insulin levels decreased, suggesting that a single session may modulate fetuin-A levels [74]. Similarly, Sakr et al [75] reported that 16 weeks of swimming exercise decreased serum fetuin-A levels and improved the homeostatic model assessment for insulin resistance (HOMA-IR) scores in a metabolic syndrome model. Malin et al [76] also reported that endurance exercise could decrease fetuin-A levels in obese patients with NAFLD.…”
Section: The Effects Of Exercise On Fetuin-amentioning
confidence: 98%
“…375,376 Studies have reported that aerobic and endurance exercise as well as swimming results in decreased Fetuin-A levels that improved glucose tolerance and reduced IR. [377][378][379] He et al, 380 have reported that exercise has a direct effect on FGF21 levels, whereas Chavez et al, 381 observed that increased plasma level of FGF21 during exercise is declined in T2DM patients. Taken together, these studies suggest that production of FGF21 varies in different metabolic conditions.…”
Section: Lifestyle Variables and Organokinesmentioning
confidence: 99%
“…Several studies have suggested that expression of certain hepatokines is modulated by exercise 375,376 . Studies have reported that aerobic and endurance exercise as well as swimming results in decreased Fetuin‐A levels that improved glucose tolerance and reduced IR 377–379 . He et al, 380 have reported that exercise has a direct effect on FGF21 levels, whereas Chavez et al, 381 observed that increased plasma level of FGF21 during exercise is declined in T2DM patients.…”
Section: Lifestyle Variables and Organokinesmentioning
confidence: 99%